4CPS-220 Patient satisfaction with pharmacist education on oral anticoagulant medication. (14th March 2021) - Murphy, D; Kieran, M; Brown, J
Abstract : Background and importance: Oral anticoagulants are internationally recognised as high risk medications that can cause significant patient harm when used in error. 1 High patient adherence to oral anticoagulant treatment is essential to avoid thrombosis or stroke. The pharmacy department has prioritised the provision of medicines education to all inpatients newly started on an oral anticoagulant. Both verbal education and a warfarin or direct acting oral anticoagulant (DOAC) booklet are provided to all patients. A DOAC booklet was developed and introduced in 2017. Aim and objectives: To assess patient satisfaction with oral anticoagulant education provided by pharmacists and to obtain feedback on the new DOAC booklet. Material and methods: The study took place over a 6 week period (February to April 2018). All patients provided with pharmacist education on an oral anticoagulant were requested to complete a patient satisfaction survey after the education session. Patients had the option to decline participation in the study. The survey assessed if the patient found the information useful, the quantity of information discussed and the medium of communication considered most beneficial. Results: 30 patients were involved in this study. 40% (n=11) of patients were prescribed warfarin, with the remaining 56% (n=17) prescribed a DOAC (apixaban n=12, rivaroxaban n=4, dabigatran n=1). All patients reported that the verbal and written information was useful and that they were happy with the amount of information discussed. 97% of patients (n=29) reported that they understood the information discussed. When asked which format of communication was most beneficial, the majority (n=16) of respondents answered both verbal and written communication. All patients (n=16) who had read the DOAC booklet reported that it was helpful. Conclusion and relevance: The results of this study demonstrated patient satisfaction with pharmacist education on newly commenced oral anticoagulants. Most education sessions were for DOACs, reflecting the change in prescribing practices and the trend away from warfarin. The preferred medium of education varied between patients. The results suggested that pharmacists should continue to use both verbal and written education to account for patient preference and understanding. Patients reported that they found the new DOAC booklet helpful. References and/or acknowledgements: Institute for Safe Medication Practices (ISMP). ISMP List of High-Alert Medications in Acute Care Setting . 2018 cited 2018 December/28 Conflict of interest: No conflict of interest